Efektivitas Bermain konstruktif dengan Metode “Building Blocks” untuk Mengembangkan Kemampuan Berpikir Kreatif pada anak usia dini - anjarsari, Irna; Linawati, Ririn; Furi, Atika Zahra; Sari, Ika Tyas Mustika; Munawaroh, Hidayatu; Hidayati, Salis Wahyu (Sentra Cendekia, 2024)
Constructive play with the Building Blocks method can provide building blocks for children to explore mathematical concepts and improve their social skills through interaction in play activities. This activity not only stimulates creativity, but also supports the development of communication and collaboration skills among children. educators pay less attention to children playing with blocks and tend to provide immediate intervention. When children create buildings from blocks, the teacher is not only an example and facilitator but can be a partner when children play with blocks. The sample of this study from institutions in one cluster, namely PAUD Herni Dwi Wulan totaling 28 children as an experimental group and PAUD Anak Ceria totaling 26 children as a control group. Research data can be quantitative and qualitative data in the form of numbers and observations during activities. The tcount result of creative thinking ability is then compared with the ttable price = 2.008, with the interpolation formula of dk = 52. Based on these calculations, it turns out that the tcount is greater than the ttable (4.147 > 2.008), thus Ho is rejected and Ha is accepted. Constructive play with the “Building Blocks” method, proven effective for improving creative thinking skills in early childhood, based on an assessment with the Independent Sample t-test which shows the results of t count greater than t table.